2018
DOI: 10.1111/wbm.12159
|View full text |Cite
|
Sign up to set email alerts
|

Effect of simulated herbivory on bellyache bush (Jatropha gossypiifolia L.) growth and implications for biological control

Abstract: Understanding the ability of invasive plants to compensate for herbivory damage is crucial for their management, but this has been poorly studied in weed biological control. Bellyache bush (Jatropha gossypiifolia L.) is an invasive weed and a target for biological control in Australia. To understand the response of bellyache bush to herbivory, we simulated herbivory damage, under field conditions, at a site in north Queensland. Two size classes, that is, seedlings and mature plants were subjected to either def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…By removing the flies after one galling event per release, exposure of the plants to the flies was limited for strict comparison with the greenhouse trials. This may not completely represent true field conditions and as a multivoltine agent, the fly's impact might be greater than measured here (Kumaran et al 2018). In Hawaii, Crofton weed has been successfully controlled by the gall fly alone, where Crofton weed has been eliminated over large tracks of land, in low rainfall areas (Bess andHaramoto 1959, 1972;Muniappan et al 2009).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…By removing the flies after one galling event per release, exposure of the plants to the flies was limited for strict comparison with the greenhouse trials. This may not completely represent true field conditions and as a multivoltine agent, the fly's impact might be greater than measured here (Kumaran et al 2018). In Hawaii, Crofton weed has been successfully controlled by the gall fly alone, where Crofton weed has been eliminated over large tracks of land, in low rainfall areas (Bess andHaramoto 1959, 1972;Muniappan et al 2009).…”
Section: Discussionmentioning
confidence: 82%
“…However, there is an increasing call not to release agents which are unlikely to be very effective (Paynter et al 2018;Raghu et al 2006) because of the risks associated with non-target effects. Therefore in addition to host specificity, the effectiveness of biocontrol agents is often assessed under controlled conditions in laboratory or greenhouse studies (Cowie et al 2017;Kumaran et al 2018;Morin et al 2009). However, under such controlled conditions the impact of the agents can be either under-or over-estimated, as these are not always representative of conditions in the field (Morin et al 2006(Morin et al , 2009Rosskopf et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Jatropha gossypiifolia is subject to herbivory and a suitable target for biological control in Australia (Kumaran et al . 2018). Simulated herbivory studies have indicated that J. gossypiifolia is susceptible to both defoliation and shoot damage.…”
Section: Discussionmentioning
confidence: 99%